A Multicenter Randomized Controlled Trial of Malignant Gastric Outlet Obstruction: Tailored Partially Covered Stents (Placed Fluoroscopically) versus Standard Uncovered Stents (Placed Endoscopically) - Ding Shi; Feng Ji; Yin-su Bao; Yong-pan Liu (Gastroenterology Research and Practice)
The aim of our study is to compare the efficacy and safety of “outlet-shape” tailored stents with standard stents for the management of distal gastric cancer causing gastric outlet obstructions (GOOs) with varying gastric cavity shapes and sizes. To determine the shape and size of the GOOs, stomach opacifications were performed using contrast media before stenting. Two basic shapes of the residual cavity of the proximal GOO were observed: cup shaped or approximately cup shaped and funnel shaped or approximately funnel shaped. Other shapes were not found. In the GOO tailored group, the size and shape of the proximal ends of the tailored stent were suited for the residual cavity of the proximal GOO. The tailored stents included large cup-shaped stents and large funnel-shaped stents. GOO tailored covered stents led to less restenosis and reintervention rates compared to standard uncovered stents but with the same survival.